PENGARUH KELENGKAPAN PRODUK, PERSEPSI HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Toko Pakan Ternak Soponyono Muneng, Gumukmas – Jember) - Zainullah, Anas Wahyu; Satoto, Eko Budi; Winahyu, Pawestri (Fakultas Ekonomi dan Bisnis, 2022)
One of the most crucial aspects of the company's advancement was the recent, rapid changed in the business world and marketing issues. To obtain a high customer interest in purchasing, we had to get a policy that could offer companies immediate incentives for using the appropriate marketing strategy. By enhancing product completeness, pricing perception, and location, the corporation could improve purchasing decisions by using one of these marketing tactics. This approach could improve consumer purchasing choices at the Soponyono Muneng Animal Feed Store. This research aimed to ascertain how product completeness, perceived price, and location affected consumers' decisions to buy at the Soponyono Muneng Animal Feed Store in Gumukmas-Jember. Product completeness, pricing perception, and location were the independent factors used in this research, while purchasing choice was the dependent variable utilized in this research. The participants of this research, which also incorporated quantitative research, were the customer base of Soponyono Muneng's Animal Feed Shop. There were 112 samples in this research, and purposive sampling was used to choose them. The analytical method used in this research was multiple linear regression by using the SPSS25 program. Based on previous research findings, the product had a significant value of 0.005 and a t-count value of 2.876, according to the t-test of completion. Then the data demonstrated that the product's completeness significantly influenced positively and consumers' purchase decisions. The price perception variable, however, had a significant value of 0.015 and a t-count value of 2.481. Then the evidence indicated that price perception greatly influenced positively and purchasing choices. The data demonstrated that the location substantially impacted positively and purchasing decisions even though the location variable had a t-value of 2.637 and a significant value of 0.010.